Analisis Fundamental untuk Memperoleh Nilai Wajar Saham SMDR dengan Metode Free Cash Flow to Equity dan Price Earning Ratio - Yudha Suntara Yauwanta (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Investors or parties who invest in shares, so far have faced obstacles in assessing the fair price of the stock to be purchased. The main cause lies in the limited knowledge or insight in conducting basic or fundamental analysis of the stocks to be purchased. The consequences that are often experienced are investing overvalued, price distortions, rushing to sell back shares so that the investment does not get optimal results. The objective of this paper contributes to analyze the fairness of SMDR's stock (PT. Samudera Indonesia, Tbk.) using the Free Cash Flow To Equity (FCFE) method and the Price Earning Ratio (PER) method, assuming constant economic growth and calculating intrinsic value using a comparison of the two methods. This research is a descriptive study using a quantitative approach. The object of this research is the stock of PT. Samudera Indonesia, Tbk (SMDR). In analyzing, the author will make a financial model with projections for the next 10 years and compare it with the current share price, to find out whether the company's shares (SMDR) are considered fairvalued, undervalued or overvalued. The use of FCFE will be more prominent as of this writing, using a discounted cash flow valuation framework. This research in the form of a fundamental analysis of SMDR shares will be conducted based on published audited financial reports for the years 2016 – 2021. The theoretical benefit of this research is to assist investors in assessing a company's shares, using the FCFE method, in determining investment decisions (buy/hold/sell).